Single Nucleotide Polymorphisms Detected and In Silico Analysis of the 5’ Flanking Sequence and Exon 1 in the Bubalus bubalis Leptin Gene - Scatà, M.C.; Grandoni, F.; Antonelli, S.; De Matteis, G.; Napolitano, Francesco (Journal of Buffalo Science, 2012)
The leptin plays a critical role in the regulation of reproductive and immune function in humans, it is at the centre of the complex networks that coordinate changes in nutritional state with many diverse aspects of mammalian biology. In this study, we have sequenced the 5’ flanking region and exon 1 of the leptin gene in buffalo, and have detected eight single nucleotide polymorphisms; we have made evidence, through in silico analysis that many of them fall within putative binding sites for transcription factors. Starting from the bovine whole genome shotgun sequence, that encodes the complete sequence of the leptin gene, we had designed primers to amplify two amplicons, so to cover the 5’ flanking and exon 1 of the leptin gene of 41 non related buffaloes. The newly sequenced buffalo fragment was submitted to profile search for transcription factor binding sites, using the MATCHTM program, focusing on the areas where the single nucleotide polymorphisms had been detected. Our analysis shows that the majority of the identified single nucleotide polymorphisms fall into the core sequence of transcription factor binding sites that regulate the expression of target genes in many physiological processes within mammalian tissues. Because the leptin gene plays an important role in influencing economic traits in cattle, the novel detected single nucleotide polymorphisms might be used in association studies to assess their potential of being genetic markers for selection.